Synthesis by Precipitation and Characterisation of Antimony Tetraoxide - Saiman, Mohd Izham (2006)
Antimony oxide has found application in various area including clarification, pigment, material synthesis and catalyst. This study investigated the influence of synthesis parameters (precipitating agent and solvent) on the formation of antimony oxide powder. Characterizations of the samples were carried out by Thermogravimetry Analysis (TGA), X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, BET surface area measurement and Scanning Electron Microscopy (SEM). Investigations on the influence of the type of precipitating agents (NaOH and NHIOH), on the formation of antimony oxide revealed that a-Sb204 was produced after the precursors were calcined. The precursors were a mixture of Sb40sC12 and Sb203 phase when precipitated with NaOH but only Sb203 phase when precipitated with NH40H. By varying the two precipitation agent, NH40H solution gave better surface areas and fine morphologies for the samples compared to NaOH solution. On the influence of solvent, ethanol gave full reflection of Sb203and different structure phase before calcination process. No phase of the antimony oxy chloride was obtained for these samples. After calcined process, all samples gave full reflection of the a-Sb204. Usage of the NaOH as a precipitating agent gave higher surface area compared to NH40H samples.